Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

Gender and Embodiment in the Contemporary Montreal Swing Dance Community - Batty, Megan (Université McGill, 2020)
"This thesis explores embodiment and gender within the contemporary Montreal swing dance community. Drawing on scholarship in musicology, dance studies, jazz studies, and gender studies, I investigate the relationship between dancers and musicians/DJs. I explore the many facets of this choreomusical conversation and trace this dialogic and collaborative relationship on the social dance floor. The contemporary community is a product of the swing revival and navigating issues of authenticity thus becomes an important consideration for dancers, musicians, and DJs alike. One product of this revival is the set of heteronormative values that underpin the contemporary community. I investigate to what extent these values are reified, challenged, or altogether subverted by participants through musical and choreomusical choices. To this end I conducted interviews with six informants, each of whom has experience as both a dancer and musician and/or DJ. Their privileged position arising from their dual experience affords them insight on the ways in which dancers and musicians/DJs function within the community. This thesis builds on existing scholarship by situating the voices of individuals with choreomusical experience in dialogue with existing scholarship, and ultimately revalues the importance of both embodied knowledge and gender within the swing community"– Author's abstract

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)
Publisher: University of Nebraska Press

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Publisher: Circuit, musiques contemporaines
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Blondie B, rappeuse des premières heures au Québec - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Wavy Wanda et Baby Blue, pionnières du rap à Montréal - Desfossés, Félix B. (Les racines du hip-hop au Québec. Tome 1, 2020)

Mouffe. Au cœur du showbiz - Dumas, Carmel; Monfette, Claudine (Éditions La Presse, 2020)
La parolière d’Ordinaire et du Mur du son, c’est elle. La muse du jeune Charlebois, c’est encore elle. La metteure en scène de spectacles mythiques (Magie rose, J’ai vu le loup, le renard, le lion) et d’innombrables galas, c’est toujours elle. « Elle », c’est Mouffe, figure légendaire du Québec en marche, née Claudine Monfette, alouette ! Diplômée de l’École nationale de théâtre, interprète de chansons en duo et de rôles d’ingénue, éternelle tête chercheuse, semeuse de bonnes idées et mentore de la relève, elle a contribué à faire de notre milieu artistique ce qu’il est. Journaux personnels de Mouffe, entrevues avec celle-ci mais aussi avec sa famille, ses amis, ses collègues : Carmel Dumas a remonté pendant plus de dix ans le fil de cette vie palpitante et trace ici le portrait d’une femme omniprésente et effacée, fantaisiste et sage. Une vieille âme enveloppée de candeur, extraordinaire survivante.
Keywords: Biography & Autobiography / Artists; Architects; Photographers

Sacred Song Sisters: Choral and Solo Vocal Church Music by Women Composers for the Lenten Revised Common Lectionary - Elliott, Lisa A. (Université du Nevada, 2020)
This document explores sacred music by women composers for the Revised Common Lectionary (RCL) of the Catholic and Christian churches. The study researches exclusively choral and vocal solo music by women composers for the church season of Lent. Other primary limitations include music in English, and music from the nineteenth century to the present. The main question answered in this document is: what sacred music has been published by women composers that may be programmed in church services? This question is answered in the included appendices. These appendices list the music by women composers appropriate for the specific RCL readings for each Sunday of Lent, as well as the holidays of Ash Wednesday, Maundy Thursday, and Good Friday. There are also appendices of choral and solo vocal pieces that are generally appropriate for the Lenten season. Every attempt was made to be as thorough as possible in identifying this music, with the understanding that no one compilation of this kind can ever be complete. Additionally, selected works by six composers are explored in this document: Emma Lou Diemer (b. 1927), Arletta O’Hearn (b. ca 1928), Jane M. Marshall (1924 – 2019), Rebecca Clarke (1886 – 1979), Violet Archer (1913 – 2000), and Undine Smith Moore (1904 – 1989). These composers are representative of the variety of styles, diversity, history, and levels of musical complexity within this body of music.
ISBN: 9798662554733
Keywords: Choir; Christ; Female; Service; Sing; Worship

Renée Claude. Donne-moi le temps - Girard, Mario (Éditions La Presse, 2020)
À l’aube des années 1960, Renée Claude fait ses débuts de chanteuse en interprétant Ferré, Béart et Brassens, mais aussi, et surtout, les siens (Ferland, Léveillée, Vigneault, DesRochers, Lelièvre). Sa rencontre avec l’auteur-compositeur Stéphane Venne, puis son association avec le parolier Luc Plamondon marqueront un point tournant dans sa carrière. Pendant plus d’une décennie, Renée Claude enchaînera les succès. « C’est notre fête aujourd’hui », « Le début d’un temps d’un nouveau », « Le tour de la terre », « Viens faire un tour », « Tu trouveras la paix », « Un gars comme toi », « Ce soir je fais l’amour avec toi » ... Au début des années 1980, alors que d’autres chanteuses de sa génération rendent les armes, Renée Claude connaît une incroyable renaissance avec un cycle d’hommages à Clémence DesRochers, Georges Brassens et Léo Ferré. Offerts aux quatre coins du monde pendant plus de 30 ans, ces spectacles confirmeront son grand talent d’interprète. Grâce à des dizaines d’entretiens, le journaliste Mario Girard retrace le fascinant parcours de plus de 50 ans de cette artiste incomparable. À travers son histoire, il raconte aussi celle du Québec qui a émergé de la Grande Noirceur pour se tailler une identité à sa mesure. Et on peut affirmer que Renée Claude y a largement contribué.
Keywords: Biography & Autobiography / Entertainment & Performing Arts; Biography & Autobiography / General; Biography & Autobiography / Music

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

Monique Leyrac : notre grande dame de la chanson québécoise du XXe siècle - Laberge, Yves (Cap-aux-Diamants : la revue d'histoire du Québec, 2020)
Un article de la revue Cap-aux-Diamants, diffusée par la plateforme Érudit.
Publisher: Les Éditions Cap-aux-Diamants inc.

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound